2013
DOI: 10.2503/jjshs1.82.131
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Loquat Accessions in Japan as Assessed by SSR Markers

Abstract: The genetic variation of loquat (Eriobotrya japonica (Thunb.) Lindl.) was characterized by SSR markers developed from apple and pear, using 94 loquat accessions in Japan. Fourteen of the 24 SSR markers derived from apple could successfully produce amplified bands in loquat, whereas 10 of the 24 SSR markers derived from pear could generate amplified bands. Nine SSR markers were chosen for evaluation of the genetic diversity among 94 loquat accessions, including 61 cultivars from Japan and other countries and 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Because 'Champagne' is homozygous-dominant for Pse-a (Hiehata et al, 2002b), it is a valuable breeding material to produce cultivars with precocious character. Also, 'Champagne' is less closely related genetically to the mentioned materials that possess pse-c derived from 'Mogi' (Fukuda et al, 2013), it may help breeders to avoid the inbreeding depression that has been reported in fruit bushes and trees such as rabbiteye blueberry (Vaccinium ashei Reede; Lyrene, 1983), persimmon (Diospyros kaki Thunb. ; Yamada, 1993), and japanese pear .…”
Section: Cross Imentioning
confidence: 99%
See 2 more Smart Citations
“…Because 'Champagne' is homozygous-dominant for Pse-a (Hiehata et al, 2002b), it is a valuable breeding material to produce cultivars with precocious character. Also, 'Champagne' is less closely related genetically to the mentioned materials that possess pse-c derived from 'Mogi' (Fukuda et al, 2013), it may help breeders to avoid the inbreeding depression that has been reported in fruit bushes and trees such as rabbiteye blueberry (Vaccinium ashei Reede; Lyrene, 1983), persimmon (Diospyros kaki Thunb. ; Yamada, 1993), and japanese pear .…”
Section: Cross Imentioning
confidence: 99%
“…Seedlings resistant to Group C with the pse-c gene have been produced by the breeding program at the Agricultural and Forestry Technical Development Center, Nagasaki, Japan. However, inbreeding depression might be a concern in breeding for Group C resistance because the number of resistant parent materials that contain pse-c (e.g., 'Mogi', 'Shiromogi') is limited, and there are close relationships among these materials (Fukuda et al, 2013). Although their descendants could be crossed or back-crossed with parents to produce a high proportion of homozygous-recessive seedlings (pse-c/pse-c) that are resistant to Group C, these crosses involve inbreeding and were therefore likely to exhibit inbreeding depression with lower tree vigor or yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soriano et al (2005) first demonstrated the usefulness of SSRs markers in genetic analysis and identification in E. japonica . Many researches utilized AFLP and SSRs markers to investigate genetic variation, diversity and identification among loquat accessions (He et al 2011; Fukuda et al 2013; Blasco et al 2014), which provided information for diversity analysis and plant breeding program. However, few molecular markers based on plastomes have been developed since completed plastid genome of E. japonica is not available, lagging behind other species of Rosaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Simple sequence repeat (SSR) is used for genetic and phylogenetic studies in many plants because of its high polymorphism and co-dominant expression (Fukuda et al, 2013;Goto-Yamamoto et al, 2013;Honsho et al, 2012). SSR markers have been established from expressed sequence tag (EST) in asparagus (Caruso et al, 2008).…”
Section: Introductionmentioning
confidence: 99%